Peranan Pendidikan Agama Kristen dalam Menangkal Penyesatan Firman Tuhan di Gereja - Sarah Wassar; Zesika Natalia Wahyudi (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
The development of digital and postmodern culture presents a major challenge to the church through the emergence of various forms of misinterpretation of God’s Word that deviate from biblical teaching. Low biblical literacy, weak spiritual discernment, and the influence of instant digital teaching mean that congregants are easily swayed by unbiblical and manipulative doctrines. This study aims to analyse the role of Christian Religious Education in countering the misinterpretation of God’s Word in the modern church. It employs a descriptive qualitative method through a literature review approach, incorporating theological and pedagogical analysis of various academic texts. The findings indicate that Christian Religious Education is capable of strengthening biblical literacy, spiritual discernment, and the steadfastness of the Christian congregation’s faith. Further findings indicate that the strengthening of theological pedagogy and digital literacy helps congregations critically confront the influence of heretical teachings. Christian Religious Education plays a vital role in preserving the purity of church doctrine through systematic and contextual faith formation. The development of Bible-based learning and digital literacy strengthens the spiritual resilience of congregations in the face of postmodern culture. The Church needs to develop theological education strategies to ensure the congregation’s faith remains steadfast in the long term. Abstrak Perkembangan budaya digital dan postmodern menghadirkan tantangan besar bagi gereja melalui munculnya berbagai bentuk penyesatan firman Tuhan yang menyimpang dari ajaran Alkitab. Rendahnya literasi Alkitabiah, lemahnya discernment rohani, serta pengaruh pengajaran digital instan menyebabkan jemaat mudah terpengaruh doktrin yang tidak alkitabiah dan bersifat manipulatif. Penelitian ini bertujuan menganalisis peranan Pendidikan Agama Kristen dalam menangkal penyesatan firman Tuhan di gereja modern. Menggunakan metode kualitatif deskriptif melalui pendekatan studi pustaka dengan analisis teologis dan pedagogis terhadap berbagai literatur ilmiah. Hasil penelitian menunjukkan Pendidikan Agama Kristen mampu memperkuat literasi Alkitabiah, discernment rohani, serta keteguhan iman jemaat Kristen. Hasil lainnya menunjukkan penguatan pedagogi teologis dan literasi digital membantu jemaat menghadapi pengaruh ajaran sesat secara kritis. Pendidikan Agama Kristen berperan penting menjaga kemurnian ajaran gereja melalui pembinaan iman yang sistematis dan kontekstual. Pengembangan pembelajaran berbasis Alkitab dan literasi digital memperkuat ketahanan spiritual jemaat menghadapi budaya postmodern. Gereja perlu mengembangkan strategi pendidikan teologis demi menjaga keteguhan iman jemaat berkelanjutan.